Method for hydrothermally synthesizing iron-doped skeleton hollow molecular sieve material by utilizing ion exchange to assist and application of iron-doped skeleton hollow molecular sieve material

Through ion exchange-assisted hydrothermal synthesis of iron-doped skeleton hollow molecular sieve materials, the problems of low efficiency and ease of inactivation of existing molecular sieve catalysts are solved, and more efficient and stable catalytic performance and longer service life are achieved. It is suitable for textile printing and dyeing wastewater treatment and other fields.

CN119680621AActive Publication Date: 2025-03-25BEIJING NORMAL UNIV AT ZHUHAI
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411866520.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

When used as catalysts, existing molecular sieves have problems such as low efficiency, easy deactivation, difficult structure control, and difficult recycling, especially in textile printing and dyeing wastewater treatment.

Method used

Ion-exchange-assisted hydrothermal synthesis is used to synthesize iron-doped skeleton hollow molecular sieve materials, and by immersing the quartz fiber support in the synthetic liquid, ion exchange and hydrothermal synthesis are performed to form an iron-doped skeleton molecular sieve with a stable hollow pore structure.

Benefits of technology

It improves the stability and selectivity of the catalyst, extends the service life, enhances the adsorption performance, and reduces the preparation cost. It is suitable for wastewater treatment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680621A_ABST
    Figure CN119680621A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an iron-doped skeleton hollow molecular sieve material through ion exchange assisted hydro-thermal synthesis, and belongs to the technical field of molecular sieves, the preparation method of the iron-doped skeleton hollow molecular sieve material comprises the following steps: mixing silica sol, sodium metaaluminate, sodium hydroxide, water and a soluble iron source, stirring and aging until complete hydrolysis, filtering, and drying to obtain an iron-doped skeleton hollow molecular sieve material; a synthetic solution is obtained; and immersing a quartz fiber carrier in the synthetic solution, reacting at 60-150 DEG C for 12-48 hours, cooling, washing, and drying. The iron-doped skeleton hollow molecular sieve material has the effects of resisting metal high-temperature sintering, inhibiting metal crystal grain growth and keeping high metal dispersity, and skeleton iron has a crystal structure which is more stable than that of a traditional impregnation method, so that a catalyst is kept stable and efficient in a reaction process; and the possibility of side reaction and the leaching rate of active components of the catalyst can be reduced, so that the catalyst has better catalytic performance and longer service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieves, and in particular relates to a method for synthesizing an iron-doped framework hollow molecular sieve material by utilizing ion exchange-assisted hydrothermal synthesis and an application thereof. Background Art

[0002] The public's concern about water pollution treatment has also gradually increased. In order to build a resource-saving, environmentally friendly society and achieve sustainable development, it is necessary to comprehensively reduce wastewater discharge and solve water pollution problems in an all-round way.

[0003] The textile printing and dyeing industry is one of the industrial sectors with large water consumption and large wastewater discharge. According to statistics, the amount of wastewater discharged by my country's printing and dyeing enterprises every day reaches 3 million to 4 million tons. Textile industrial wastewater generally contains suspended solids, grease, fiber scraps, surfactants and various dyes. For example, cotton textile wastewater often contains cotton scraps and pulp, wool textile wastewater often contains grease; printing and dyeing wastewater often contains pulp, dyes, auxiliaries and various organic matter. Textile wastewater has the characteristics of large quantity, complex composition and heavy economic load for treatment. Even after treatment, it may still cause residues to gradually accumulate in the natural environment. At present, common textile wastewater treatment methods have certain limitations: the scope of application of biodegradation methods is limited and difficult to apply on a large scale; high-cost methods such as electrochemical and membrane filtration have unstable treatment efficiency and are not suitable for large-scale promotion. In contrast, adsorption and catalytic oxidation methods have attracted much attention due to their simplified process and high efficiency. As the key basis of adsorption method, although adsorbents have been used in textile wastewater treatment, their activity and stability still have room for improvement.

[0004] In the face of these challenges, innovative and sustainable approaches are needed to improve wastewater treatment technology in the textile printing and dyeing industry to ensure the health of the ecological environment and the sustainable development of human society. Summary of the invention

[0005] In order to solve the problems of low efficiency, easy deactivation, difficult structure control, and difficulty in recycling when the existing molecular sieve is used as a catalyst, the present invention proposes a method and application thereof for the hydrothermal synthesis of iron-doped skeleton hollow molecular sieve materials assisted by ion exchange. Compared with the conventional molecular sieve preparation method, the novel iron-doped skeleton hollow molecular sieve material prepared by the present invention directly uses unpretreated quartz fiber as raw material, simplifies the preparation process, does not need to be pretreated with 3-aminopropyltrimethoxysilane (APTMS), toluene, etc., can form a dense molecular sieve film on the fiber surface, and selects a suitable temperature for hydrothermal synthesis, can control the clustering phenomenon of the molecular sieve surface particles, and finally makes the material have a stable hollow pore structure, can greatly improve mass transfer efficiency, reduce leaching phenomenon and improve material stability. At the same time, the iron-doped skeleton hollow molecular sieve material of the present invention also has a large specific surface area, good thermal stability and chemical stability, combined with its structural performance, can effectively play its performance in the fields of sewage treatment.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] The present invention provides a method for synthesizing an iron-doped framework hollow molecular sieve material by ion exchange-assisted hydrothermal synthesis, comprising the following steps:

[0009] The silica sol, sodium aluminate, sodium hydroxide, water and a soluble iron source are mixed, stirred and aged until completely hydrolyzed to obtain a synthetic solution;

[0010] The quartz fiber carrier is immersed in the synthetic liquid (so that the quartz fiber and the synthetic liquid can fully exchange ions, thereby making the iron skeleton in the molecular sieve material evenly distributed), reacted at 60-150° C. for 12-48 hours, washed and dried after cooling to obtain the iron-doped skeleton hollow molecular sieve material.

[0011] The preparation steps of the synthetic liquid are as follows: sodium aluminate (NaAlO2), sodium hydroxide (NaOH) and a soluble iron source are mixed, water is added, and stirred to obtain a clear and transparent solution, silica sol is added while stirring, and stirred and aged until it is completely hydrolyzed to obtain a synthetic liquid.

[0012] The mass ratio of the silica sol, sodium aluminate, sodium hydroxide, water and soluble iron source is (5.00-10.00): (2.00-6.80): (20.00-55.00): (190.00-260.00): (3.80-9.00).

[0013] Preferably, the mass ratio of the silica sol, sodium aluminate, sodium hydroxide, water and soluble iron source is (8.00-10.00):(2.00-4.00):(48.00-55.00):(200.00-240.00):(3.80-5.20), (5.00-8.00):(5.00-6.80):(20.00-30.00):(200.00-260.00):(4.00-5.50) or (5.00-10.00):(3.50-4.70):(35.00-44.00):(190.00-260.00):(6.00-9.00). The present invention explores the mass ratios of different silica sols, sodium aluminate, sodium hydroxide, water and soluble iron sources and finds that the iron skeleton hollow molecular sieve material synthesized at a specific mass ratio has excellent morphology and performance. Taking the silicon-aluminum ratio in the molecular sieve synthesis liquid as an example, if the ratio is too low, the molecular sieve grains will grow too large and other molecular sieve crystal forms (such as type A molecular sieve) will be generated. If the ratio is too high, it is easy to generate mesoporous molecular sieve crystals and P-type molecular sieve phases, and it is impossible to form a dense iron skeleton molecular sieve structure, which leads to a significant decrease in the performance of the molecular sieve.

[0014] Exemplarily, the soluble iron source is FeSO4·7H2O.

[0015] The drying temperature is 100-150° C. and the drying time is 12-48 hours.

[0016] Ojasite zeolite molecular sieves have important applications in adsorption, separation, catalysis and other fields due to their developed three-dimensional pore system and large pore volume. As a six-membered silicon-aluminum ring molecular sieve, its basic structural unit is similar to the crystal structure of diamond. Usually, Si / A1 within 1-1.5 is called X-type molecular sieve, and Si / A1 greater than 1.5 is called Y-type molecular sieve. Both low-silicon X-type molecular sieves and high-silicon Y-type molecular sieves are the main components of the most widely used petroleum processing catalysts. At the same time, they are also important adsorbents for gas adsorption, separation and purification. Ojasite zeolite molecular sieves have structural advantages such as high temperature resistance, resistance to chemical and biological corrosion, good mechanical strength and catalytic performance, and regular pore structure. Compared with NaA and MFI molecular sieves, ojasite zeolite molecular sieves have larger pore sizes and three-dimensional cage-like pore structures, so that larger separation selectivity and permeation flux can be obtained. Due to the presence of metal elements in the molecular sieve framework structure, there are cations (such as Na) in the framework of the ojasite zeolite molecular sieve to balance the charge. + ), this characteristic makes it exhibit unique and excellent performance in ion exchange, catalysis and adsorption. In addition, the high metal content in the faujasite zeolite framework and the highly dispersed Na +It has a high polarity and can selectively adsorb and separate polar molecules. The present invention uses hydrothermal synthesis combined with ion exchange to successfully allow iron elements to enter the molecular sieve skeleton structure during the molecular sieve preparation process, partially replacing the aluminum element therein, so as to regulate the surface properties of the carrier catalyst. Compared with the common impregnation technology, the iron-doped skeleton molecular sieve prepared by the ion exchange method used in the present invention not only has the effect of resisting high-temperature sintering of metals, inhibiting the growth of metal grains, and maintaining high metal dispersion, but also the skeleton iron has a more stable crystal structure than the traditional impregnation method, which is beneficial to ensure that the catalyst remains stable and efficient during the reaction process, and can reduce the possibility of side reactions and the leaching rate of the catalyst active components, thereby having better catalytic performance and longer service life.

[0017] Hollow molecular sieve has a unique hollow channel structure. When used as an adsorbent, catalyst or catalyst carrier, especially in the reaction process with macromolecules, the hollow pore structure provides a convenient fluid channel, which is conducive to the transfer of reactants and products, and can improve contact efficiency. At the same time, combined with the microporous structure of the molecular sieve itself and the mesoporous structure formed by grain stacking, the hierarchical aperture structure of the hollow molecular sieve can control the diffusion path length and reduce the leakage of active components, while inhibiting the deposition of coke during the reaction, thereby improving the stability and selectivity of the catalyst and achieving the purpose of extending the service life. The present invention combines the advantages of the eight-jasperite iron-doped skeleton molecular sieve material with the hollow molecular sieve through continuous optimization of the preparation process. The prepared hollow iron-doped skeleton molecular sieve material has the characteristics of strong adsorption performance, good stability, low preparation cost, high mechanical strength, and large specific surface area, and has better catalytic performance and service life than general catalysts. Based on the needs of textile printing and dyeing organic wastewater treatment technology, the iron-doped skeleton hollow molecular sieve material prepared by the present invention can be combined with catalytic wet hydrogen peroxide oxidation technology (CWPO) to further expand its application prospects in the field of industrial wastewater degradation.

[0018] The second technical solution of the present invention:

[0019] The present invention provides an iron-doped framework hollow molecular sieve material prepared according to the method.

[0020] The iron-doped framework hollow molecular sieve material prepared by the present invention is a novel iron-doped framework hollow molecular sieve material, which has a stable hollow structure, and this structure can reduce resistance, is beneficial to the transfer of reactants and products, can reduce the occurrence of side reactions and the leaching of active components of the catalyst, and has better catalytic performance and longer service life.

[0021] The third technical solution of the present invention:

[0022] The present invention also provides application of the iron-doped framework hollow molecular sieve material in treating textile printing and dyeing organic wastewater.

[0023] The fourth technical solution of the present invention:

[0024] The present invention also provides a method for treating textile printing and dyeing organic wastewater, which comprises adding the iron-doped framework hollow molecular sieve material into the textile printing and dyeing organic wastewater and reacting continuously at 30-60° C. for 3 hours.

[0025] Preferably, in the method for treating textile printing and dyeing organic wastewater, the dosage of the iron-doped framework hollow molecular sieve material is 2.0 g / L (ie, each liter of textile printing and dyeing organic wastewater contains 2.0 g of the iron-doped framework hollow molecular sieve material).

[0026] Compared with the prior art, the present invention has the following advantages and technical effects:

[0027] (1) The novel iron-doped skeleton hollow molecular sieve material prepared by the present invention has a stable hollow structure, which can reduce resistance, facilitate the transfer of reactants and products, reduce the occurrence of side reactions and the leaching of active components of the catalyst, and has better catalytic performance and longer service life;

[0028] (2) The novel iron-doped skeleton hollow molecular sieve material prepared by the present invention has a unique hollow fiber structure. Compared with the commonly used molecular sieves, it has the advantages of large specific surface area, good thermal stability and chemical stability. It can effectively exert its performance in the fields of sewage treatment, so that no toxic or harmful by-products are produced during the entire reaction process, thereby realizing the green and efficient conversion of sewage.

[0029] (3) The process of preparing the novel iron-doped hollow molecular sieve material of the present invention is simple and does not require pretreatment of the quartz fiber, which is conducive to simplifying the preparation process, controlling the finished product structure and reducing the preparation cost, thereby improving the application prospects of faujasite zeolite molecular sieves in the industrial field. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0031] Figure 1 This is an electron microscope image of the fiber cross-section of the molecular sieve material prepared in Example 1.

[0032] Figure 2 This is an electron microscope image of the fiber surface of the molecular sieve material prepared in Example 1.

[0033] Figure 3 This is the energy dispersive X-ray spectrum of the molecular sieve material prepared in Example 1. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0040] All raw materials used in the examples of the present invention are purchased from the market. For example, silica sol is purchased from Shanghai Huicheng Biological Co., Ltd.; quartz fiber is purchased from Shanghai Xinhu Experimental Equipment Co., Ltd.

[0041] In the present invention, when calculating the degradation rate of methylene blue, the absorbance of the solution is measured using an ultraviolet-visible spectrophotometer, and the degradation rate of methylene blue is calculated according to the formula: methylene blue degradation rate (%) = (initial absorbance - absorbance) / initial absorbance × 100%.

[0042] In the present invention, the leaching rate of the active component of the chemical agent is calculated as follows: metal concentration of the active component in the solution after the reaction (g / L) × solution volume (L) / (mass fraction of the active component metal in the material (obtained by the mass ratio of material preparation) × material addition concentration (g / L) × solution volume (L)) × 100%.

[0043] In some embodiments of the present invention, a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis is provided, comprising the following steps:

[0044] Mix sodium aluminate, sodium hydroxide and a soluble iron source, add water, stir until a clear and transparent solution is obtained, add silica sol while stirring, stir and age until complete hydrolysis, and obtain a synthetic solution;

[0045] The quartz fiber carrier is immersed in the synthetic solution, reacted at 60-150° C. for 12-48 hours, washed and dried after cooling to obtain the iron-doped framework hollow molecular sieve material.

[0046] In some embodiments of the present invention, the mass ratio of silica sol, sodium aluminate, sodium hydroxide, water and soluble iron source is (5.00-10.00):(2.00-6.80):(20.00-55.00):(190.00-260.00):(3.80-9.00). For example, the mass ratio of silica sol, sodium aluminate, sodium hydroxide, water and soluble iron source can be (8.00-10.00):(2.00-4.00):(48.00-55.00):(200.00-240.00):(3.80-5.20), or (5.00-8.00):(5.00-6.80):(20.00-30.00):(200.00-260.00):(4.00-5.50), or (5.00-10.00):(3.50-4.70):(35.00-44.00):(190.00-260.00):(6.00-9.00).

[0047] In some embodiments of the present invention, the soluble iron source is FeSO4·7H2O.

[0048] In some embodiments of the present invention, the drying temperature is 100-150° C. and the drying time is 12-48 hours.

[0049] The novel iron-doped skeleton hollow molecular sieve prepared by the method of the present invention has a large specific surface area, uniform pore structure, and good thermal stability and mechanical stability, and can be applied in many fields such as adsorption separation, membrane reaction, catalysis, and sensors. The hollow pore structure is conducive to shortening the diffusion path, improving the conduction efficiency, and reducing particle leaching, so as to improve the stability and selectivity of the material and improve the sewage purification efficiency, and can be innovatively applied to the sewage treatment field.

[0050] Compared with the MFI molecular sieve preparation method, the present invention does not need to prepare seed crystals in advance, can be directly converted, and is convenient and fast. At the same time, compared with other faujasite zeolite molecular sieve conversion preparation methods, the present invention can directly use unpretreated quartz fiber as a raw material due to the addition of iron to increase polarity, simplifying the preparation process, and does not need to use 3-aminopropyltrimethoxysilane (APTMS), toluene, etc. for pretreatment, and can form a dense molecular sieve membrane on the fiber surface, and select a suitable temperature for hydrothermal synthesis, which can control the clustering phenomenon of particles on the molecular sieve surface, and finally make the material have a stable hollow pore structure, which can greatly improve the mass transfer efficiency, reduce the leaching phenomenon and improve the material stability.

[0051] The present invention obtains a faujasite-type molecular sieve, which is a six-membered silicon-aluminum ring molecular sieve, and its basic structural unit is similar to the crystal structure of diamond. Due to the presence of metal elements in the molecular sieve framework structure, the molecular sieve prepared by the present invention has charge-balancing cations (such as Na + ), this characteristic makes the obtained material have more acidic and active sites, more structural defects, can better combine with reactants in the reaction, and show unique and excellent performance in catalysis and adsorption.

[0052] Compared with ZSM-5 (MFI molecular sieve), the faujasite molecular sieve obtained by the present invention has a larger pore size and a three-dimensional cage-like pore structure, thereby obtaining a larger separation selectivity and permeation flux. In addition, the high metal element content in the faujasite molecular sieve framework and the highly dispersed Na + This makes it highly polar and can selectively adsorb and separate polar molecules.

[0053] Aiming at the problem that iron loaded on the surface of a molecular sieve by an impregnation method easily forms oxides with air, which reduces the charge on the catalyst surface and reduces the acidity of the catalyst, the present invention allows the iron element to enter the molecular sieve framework structure during the molecular sieve preparation process. The iron element exists in the molecular sieve framework in the form of ions or atoms, partially replaces the aluminum element therein, and forms chemical bonds with other atoms (such as Si, O, etc.) in the framework. The surface properties of the carrier catalyst are regulated by controlling the iron content of the framework, so that the charge carried by the catalyst material as a whole is stronger, which is conducive to the catalytic reaction.

[0054] The active component iron of the catalyst prepared by impregnation or ion exchange is present on the surface of the molecular sieve, and the interaction force with the carrier is weak, and it is easy to fall off during the reaction, causing the risk of rapid deactivation of the catalyst and secondary pollution. Compared with the common impregnation technology, the iron-doped skeleton molecular sieve prepared by the ion exchange method adopted in the present invention not only has the effect of resisting high-temperature sintering of metals, inhibiting the growth of metal grains, and maintaining high dispersion of metals, but also the skeleton iron has a more stable crystal structure than the traditional impregnation method, which is conducive to ensuring that the catalyst remains stable and efficient during the reaction, and can reduce the possibility of side reactions and the leaching rate of the active components of the catalyst, so as to have better catalytic performance and longer service life.

[0055] The iron-doped framework hollow molecular sieve material prepared by the present invention can be used to treat textile printing and dyeing organic wastewater. In the embodiments of the present invention, wastewater containing methylene blue is used as an example.

[0056] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.

[0057] The technical solution of the present invention is further illustrated by the following embodiments.

[0058] Example 1

[0059] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0060] (1) 51.50 g of NaOH, 3.00 g of NaAlO2 and 4.50 g of FeSO4·7H2O were placed in a beaker, 220.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 9.00 g of silica sol was added while stirring. The obtained solution was stirred and aged for 1.5 hours to obtain a synthetic solution;

[0061] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.3 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 65 ° C for 24 hours;

[0062] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0063] (4) The washed solid is placed in an oven and dried at 120° C. for 24 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0064] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst (i.e., the new iron-doped framework hollow molecular sieve, the same below) was 2 g / L, and the reaction was continued at 30°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 96%, and the leaching rate of the catalyst active components was 1.2%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0065] from Figure 1 and Figure 2 It can be seen that the iron skeleton molecular sieve material molecular sieve prepared by the present invention has a hollow structure as a whole, the molecular sieve grains are relatively small and evenly distributed, and the molecular sieve grains are densely stacked to form a self-supporting tubular structure. The molecular sieve crystal itself has a three-dimensional cage-like microporous structure, and the grains are stacked to form a mesoporous structure. In addition, the macroporous structure of the hollow tubular structure and the multi-scale pore structure are combined, so that a larger separation selectivity and permeation flux can be obtained at the same time. In addition, the high metal element content in the molecular sieve skeleton and the highly dispersed Na + This makes it highly polar and can selectively adsorb and separate polar molecules.

[0066] The energy dispersion X-ray spectrum of the molecular sieve material prepared in Example 1 is shown in Figure 3 It can be seen that the molecular sieve presents a strong Fe element signal and the iron element is evenly distributed in the molecular sieve framework. During the preparation of the molecular sieve, the iron element enters the molecular sieve framework structure. The iron element exists in the molecular sieve framework in the form of ions or atoms, partially replacing the aluminum element therein, and forming chemical bonds with other atoms in the framework (such as Si, O, etc.). Therefore, it can be evenly dispersed and remain stable during use, reducing leaching, so that the overall charge of the catalyst material is stronger, which is conducive to the catalytic reaction.

[0067] It can be seen from the electron microscope image and the energy dispersive X-ray spectrum that the hollow molecular sieve material prepared by the method of the present invention has uniform grain distribution and relatively small grains, which is beneficial to improving the molecular sieve material's resistance to metal high-temperature sintering.

[0068] Example 2

[0069] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0070] (1) 48.00 g of NaOH, 2.00 g of NaAlO2 and 3.80 g of FeSO4·7H2O were placed in a beaker, 200.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 8.00 g of silica sol was added while stirring. The obtained solution was stirred and aged for 2 hours to obtain a synthetic solution;

[0071] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.3 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 60° C. for 48 hours;

[0072] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0073] (4) The washed solid was placed in an oven and dried at 110° C. for 48 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0074] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 30°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 95%, and the leaching rate of the catalyst active components was 1.0%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0075] Example 3

[0076] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0077] (1) 55.00 g of NaOH, 4.00 g of NaAlO2 and 5.20 g of FeSO4·7H2O were placed in a beaker, 240.0 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 10.00 g of silica sol was added while stirring. The obtained solution was stirred and aged for 1 hour to obtain a synthetic solution;

[0078] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.3 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 70° C. for 24 hours;

[0079] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0080] (4) The washed solid is placed in an oven and dried at 120° C. for 24 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0081] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 30°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 97%, and the leaching rate of the catalyst active components was 1.5%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0082] Example 4

[0083] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0084] (1) 25.00 g of NaOH, 5.90 g of NaAlO2 and 4.75 g of FeSO4·7H2O were placed in a beaker, 200.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 6.50 g of silica sol was added while stirring. The obtained solution was stirred and aged for 4 hours to obtain a synthetic solution;

[0085] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.1 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 100 °C for 16 hours;

[0086] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0087] (4) The washed solid was placed in an oven and dried at 120° C. for 36 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0088] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 40°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 97%, and the leaching rate of the catalyst active components was 1.3%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0089] Example 5

[0090] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0091] (1) 20.00 g of NaOH, 5.00 g of NaAlO2 and 4.00 g of FeSO4·7H2O were placed in a beaker, 180.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 5.00 g of silica sol was added while stirring. The obtained solution was stirred and aged for 3 hours to obtain a synthetic solution;

[0092] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.1 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 80° C. for 24 hours;

[0093] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0094] (4) The washed solid was placed in an oven and dried at 100° C. for 48 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0095] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 40°C for 3 hours. The degradation efficiency of methylene blue was maintained above 95%, and the leaching rate of the catalyst active components was 1.0%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0096] Example 6

[0097] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0098] (1) 30.00 g of NaOH, 6.80 g of NaAlO2 and 5.50 g of FeSO4·7H2O were placed in a beaker, 220.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 8.00 g of silica sol was added while stirring. The obtained solution was stirred and aged for 5 hours to obtain a synthetic solution;

[0099] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.1 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 140° C. for 12 hours;

[0100] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0101] (4) The washed solid is placed in an oven and dried at 150° C. for 24 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0102] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 40°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 97%, and the leaching rate of the catalyst active components was 1.6%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0103] Example 7

[0104] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0105] (1) 39.50 g of NaOH, 4.10 g of NaAlO2 and 7.50 g of FeSO4·7H2O were placed in a beaker, 225.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 7.5 g of silica sol was added while stirring. The obtained solution was stirred and aged for 2 hours to obtain a synthetic solution;

[0106] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.2 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 125° C. for 30 hours;

[0107] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0108] (4) The washed solid was placed in an oven and dried at 130° C. for 15 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0109] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 60°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 99%, and the leaching rate of the catalyst active components was 2.0%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0110] Example 8

[0111] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0112] (1) 35.00 g of NaOH, 3.50 g of NaAlO2 and 6.00 g of FeSO4·7H2O were placed in a beaker, 190.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 5 g of silica sol was added while stirring. The obtained solution was stirred and aged for 1 hour to obtain a synthetic solution;

[0113] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.2 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 100 ° C for 48 hours;

[0114] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0115] (4) The washed solid is placed in an oven and dried at 120° C. for 24 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0116] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 60°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 98%, and the leaching rate of the catalyst active components was 1.4%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0117] Example 9

[0118] This embodiment provides a method for synthesizing an iron-doped framework hollow molecular sieve material using ion exchange-assisted hydrothermal synthesis:

[0119] (1) 44.00 g of NaOH, 4.70 g of NaAlO2 and 9.00 g of FeSO4·7H2O were placed in a beaker, 260.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 10 g of silica sol was added while stirring. The obtained solution was stirred and aged for 3 hours to obtain a synthetic solution;

[0120] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.2 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 150 ° C for 24 hours;

[0121] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0122] (4) The washed solid was placed in an oven and dried at 140° C. for 12 hours to obtain a novel iron-doped framework hollow molecular sieve.

[0123] The performance of the new iron-doped framework hollow molecular sieve material prepared in this embodiment was tested, and the test conditions were as follows: the concentration of methylene blue solution was 2.5 mg / L, the concentration of hydrogen peroxide solution was 5 mmol / L, the amount of catalyst was 2 g / L, and the reaction was continued at 60°C for 3 hours. The degradation efficiency of methylene blue was maintained at more than 99%, and the leaching rate of the catalyst active components was 2.7%. The new iron-doped framework hollow molecular sieve material prepared in this embodiment has good catalytic degradation performance.

[0124] Comparative Example 1

[0125] The same as Example 7, except that FeSO4·7H2O is not added in step (1), that is, the molecular sieve material prepared in this comparative example is not doped with iron.

[0126] The performance of the undoped iron molecular sieve material prepared in this comparative example was tested, and the test conditions were as follows: the concentration of the methylene blue solution was 2.5 mg / L, the concentration of the hydrogen peroxide solution was 5 mmol / L, the amount of the catalyst (i.e., the undoped iron molecular sieve material) was 2 g / L, the reaction was continued at 60°C for 3 hours, and the methylene blue degradation efficiency was maintained at about 50%.

[0127] Comparative Example 2: No silica sol was added

[0128] (1) 48.00 g of NaOH, 2.00 g of NaAlO2 and 3.80 g of FeSO4·7H2O were placed in a beaker, 200.00 g of deionized water was added, and the mixture was stirred with a magnetic stirrer. The resulting solution was stirred and aged for 2 hours to obtain a synthetic solution;

[0129] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.3 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 60° C. for 48 hours;

[0130] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0131] (4) The washed solid was placed in an oven and dried at 110° C. for 48 hours, but it was found that no formed molecular sieve material could be obtained.

[0132] Reasons for the failure of the preparation of Comparative Example 2: Silica sol is a high-quality silicon source for synthesizing iron skeleton molecular sieves. The molecular sieve synthesized using silica sol has the characteristics of high crystallinity, regular morphology and good dispersibility, and exhibits excellent catalytic performance. Silica sol can provide a skeleton structure and active centers during the synthesis of molecular sieves, and the morphology and pore structure of the molecular sieve can be controlled by adjusting the properties and dosage of silica sol. The only difference between Comparative Example 2 and Example 2 is that silica sol is not added in step (1), resulting in the loss of the molecular sieve skeleton structure so that the molecular sieve material cannot be formed.

[0133] Comparative Example 3

[0134] The same as Example 1, except that FeSO4·7H2O is not added in step (1), but the common impregnation technology is used to load the iron species in step (4), and the specific method is as follows:

[0135] (1) 51.50 g of NaOH and 3.00 g of NaAlO2 were placed in a beaker, 220.00 g of deionized water was added, and after mixing, a magnetic stirrer was used to stir until a clear and transparent solution was obtained, and 9.00 g of silica sol was added while stirring. The obtained solution was stirred and aged for 1.5 hours to obtain a synthetic solution;

[0136] (2) The obtained synthetic solution was transferred to the polytetrafluoroethylene liner of a 200 mL stainless steel reactor, and 0.3 g of the quartz fiber carrier was immersed in the synthetic solution, and the reaction was carried out in an oven at 65 ° C for 24 hours;

[0137] (3) taking out the stainless steel reactor and cooling it to room temperature, taking out the solid and washing it with deionized water;

[0138] (4) The washed solid and 4.50 g of FeSO4·7H2O were added to a blue-mouth bottle and deionized water was added to 50 mL. The blue-mouth bottle was then placed in a shaker at 200 rpm for 1 h.

[0139] (5) The solid in the blue-mouth bottle is taken out and washed with deionized water. The washed solid is placed in an oven and dried at 120° C. for 24 hours to obtain an iron-loaded molecular sieve prepared by a common impregnation technique.

[0140] The performance of the iron-loaded molecular sieve material prepared in this comparative example was tested, and the test conditions were as follows: the concentration of the methylene blue solution was 2.5 mg / L, the concentration of the hydrogen peroxide solution was 5 mmol / L, the amount of the catalyst was 2 g / L, and the reaction was continued at 30°C for 3 hours. The degradation efficiency of methylene blue remained at about 85%, but after a period of use, the catalytic efficiency of the catalyst was significantly reduced, and the leaching rate of the active component reached more than 20%.

[0141] Reasons for performance degradation and poor stability of comparative example 3: The iron-doped skeleton molecular sieve prepared by ion exchange method not only has the effect of resisting metal high temperature sintering, inhibiting metal grain growth, and maintaining high metal dispersion, but also the skeleton iron has a more stable crystal structure than the common impregnation method, which is conducive to ensuring that the catalyst remains stable and efficient during the reaction. However, the iron-loaded molecular sieve prepared by the common impregnation technique in this comparative example, since only part of the iron species is loaded on the inside and surface of the molecular sieve during the impregnation process, the poor loading effect leads to significantly low catalytic degradation performance. And the interaction force between the active component and the carrier is low, and it is easy to fall off during the reaction, resulting in the loss of active components, making the catalyst poor in stability, and there is a risk of secondary pollution.

[0142] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for synthesizing an iron-doped framework hollow molecular sieve material by ion exchange-assisted hydrothermal synthesis, characterized in that: The following steps are involved: The silica sol, sodium aluminate, sodium hydroxide, water and a soluble iron source are mixed, stirred and aged until completely hydrolyzed to obtain a synthetic solution; The quartz fiber carrier is immersed in the synthetic solution, reacted at 60-150° C. for 12-48 hours, washed and dried after cooling to obtain the iron-doped framework hollow molecular sieve material.

2. The method for synthesizing an iron-doped framework hollow molecular sieve material by ion exchange-assisted hydrothermal synthesis according to claim 1, characterized in that: The preparation steps of the synthetic liquid are as follows: sodium aluminate, sodium hydroxide and a soluble iron source are mixed, water is added, and stirred to obtain a clear and transparent solution, silica sol is added while stirring, and the mixture is stirred and aged until it is completely hydrolyzed to obtain a synthetic liquid.

3. The method for synthesizing an iron-doped framework hollow molecular sieve material by ion exchange-assisted hydrothermal synthesis according to claim 2, characterized in that: The mass ratio of the silica sol, sodium aluminate, sodium hydroxide, water and soluble iron source is (5.00-10.00): (2.00-6.80): (20.00-55.00): (190.00-260.00): (3.80-9.00).

4. The method for synthesizing an iron-doped framework hollow molecular sieve material by ion exchange-assisted hydrothermal synthesis according to claim 3, characterized in that: The mass ratio of the silica sol, sodium aluminate, sodium hydroxide, water and soluble iron source is (8.00-10.00): (2.00-4.00): (48.00-55.00): (200.00-240.00): (3.80-5.20), (5.00-8.00): (5.00-6.80): (20.00-30.00): (200.00-260.00): (4.00-5.50) or (5.00-10.00): (3.50-4.70): (35.00-44.00): (190.00-260.00): (6.00-9.00).

5. The method for synthesizing an iron-doped framework hollow molecular sieve material by ion exchange-assisted hydrothermal synthesis according to claim 3, characterized in that: The soluble iron source is FeSO4·7H2O.

6. The method for synthesizing an iron-doped framework hollow molecular sieve material by ion exchange-assisted hydrothermal synthesis according to claim 1, characterized in that: The drying temperature is 100-150° C. and the drying time is 12-48 hours.

7. An iron-doped framework hollow molecular sieve material, characterized in that: Prepared according to the method according to any one of claims 1 to 6.

8. Use of the iron-doped framework hollow molecular sieve material according to claim 7 in treating textile printing and dyeing organic wastewater.

9. A method for treating textile printing and dyeing organic wastewater, characterized in that: The iron-doped framework hollow molecular sieve material according to claim 7 is added to textile printing and dyeing organic wastewater, and the reaction is continuously carried out at 30-60° C. for 3 hours.

10. The method for treating textile printing and dyeing organic wastewater according to claim 9, characterized in that: The dosage of the iron-doped framework hollow molecular sieve material is 2 g / L.

Citation Information

Patent Citations

  • Granular FeY molecular sieve and preparing method thereof

    CN102745713A

  • MFI-type silicon aluminum molecular sieve / aluminum fiber composite material, as well as preparation method and application thereof

    CN103301875A

  • High-aspect-ratio hollow molecular sieve fiber and preparation method thereof

    CN105603579A

  • Molecular sieve-type Fenton catalyst for elimination of organic dye pollution and high efficiency synthesis method thereof

    CN106732747A

  • Synthesis method of metal modified M-MFI molecular sieve membrane

    CN114560474A